Market Selection and Regional Diversification - Empirical Regularities from German Panel-Data - Florian Noseleit (European Regional Science Association (ERSA), 2010)
Several theoretical approaches to explaining economic growth focus on externalities arising from interactions between economic agents. A frequently discussed source of such externalities is regional diversity of the industry structure. A large number of empirical studies support the argument that regional diversity can be beneficial to regional employment, innovation, and economic stability. It is not particularly surprising that diversity in the industry structure can be assumed to depend, in part, on the activity of new businesses. To date, however, little is known about the roles and paths new businesses take in the diversification of the industry structure. The central questions that this paper attempts to answer are how the market selection process influences the diversity of entries and how start-up activity influences diversity in the region and beyond. For an analysis of diversity patterns, we use regional data for West Germany over a 27-year period that includes specifics about employment at the industry level and allows us to distinguish and follow entry cohorts over time. Compared with the large amount of literature analyzing whether diversity or specialization is conducive to regional development, the literature discussing trends of regional diversification is rather limited. The preliminary results of this study can be summarized as follows. On the whole, regional diversity moderately increased over the last decades. Regional diversity and region size are related via an inverse u-shape. Establishment scale is negatively related to diversity. In addition, evidence supports that regional diversity increases with the number of entries but decreases with the number of exits. Modest specialization is positively associated. Certain empirical regularities for the role of entries are: Employment diversity in entries is increasing over time at the national level, while diversity at the regional level is decreasing on average. This antipodal development of diversity can be explained by a market selection favoring a diverse set of specializations at the regional level. Despite the decrease in regional diversity in entry cohorts over time, these entries contribute to an increase in total regional diversity due to a selection within entry cohorts that substantially differs from the existing regional industry structure.
Keywords: R11; R12; L11; O11; 330; Diversity; Specialization; Entries; Market Selection